Penggunaan Non-Invasive Ventilation pada Pasien COVID-19 - Kurniawaty, Juni; Adiyanto, Bowo; Sadewo, Yuri (Jurnal Komplikasi Anestesi, 2021)
COVID-19 patients with acute respiratory distress require hospitalization and require invasive and/or non-invasive mechanical ventilation support. NonInvasive Ventilation (NIV) is used in cases requiring escalation of standard oxygen therapy to a higher level. NIV can also reduce early intubation, but long-term use of NIV is not recommended. NIV also does not decrease intubation rates. We report a 52-year-old female patient with a confirmed diagnosis of severe COVID-19. Our patient was admitted to the ICU with the use of HFNC and NIV during treatment. The use of NIV at the right time could determine the patient's prognosis. Persistent weaning of NIV could maintain PO2 and reduce the patient's oxygen fraction requirements. This patient’s condition could improve and become a survivor of COVID-19.